Pendidikan Anak (Tarbiyatul Awlad) dalam Al-Qur’an (Q.S Luqman 12-19 dan Q.S An-Nur 58-60): Kajian Tafsir Tematik - Permata, Dia; Ulhaq, Farhan; Julianti, Sherly; Karnedi, Rozian (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Children’s education (tarbiyah al-awlad) in Islam is deeply rooted in the teachings of the Qur’an, emphasizing the development of faith, character, worship, and social responsibility. Qur’anic guidance offers a timeless foundation for nurturing righteous and responsible individuals. Objective: This study aims to examine the thematic interpretation of children's education in the Qur’an, focusing specifically on Surah Luqman (verses 12–19) and Surah An-Nur (verses 58–60), in order to extract educational values and principles. Method: The research adopts a literature review and documentation approach for data collection. Data analysis was conducted through a descriptive-analytical method and thematic interpretation, focusing on identifying key messages and values related to child education in the selected verses. Result: The study reveals that the Qur’anic approach to children's education emphasizes monotheism (tauhid), ethical behavior, obedience to parents, regular worship, moral responsibility, patience, and social etiquette. Luqman's advice to his son in Surah Luqman encapsulates holistic child education, while Surah An-Nur provides guidance on modesty and respect in family interactions. Conclusion: The Qur’an provides comprehensive educational principles that are highly relevant for guiding children’s development in faith, character, and social behavior. These teachings serve as a moral and spiritual framework for nurturing future generations. Contribution: This study offers a foundational reference for the development of child education programs grounded in Qur’anic values, contributing to Islamic pedagogy and curriculum design that is both spiritually and ethically informed.